Numerical analysis of the traction effect on reciprocating seals in the hydraulic actuator. (March 2020) - Peng, Chao; Ouyang, Xiaoping; Guo, Shengrong; Zhou, Qinghe; Yang, Huayong
Abstract: Reciprocating seals guarantee the normal work of hydraulic actuators. Friction in the rod-seal contact pair acts as a tractive force, changing the seal's deformation and contact-pressure distribution. However, previous studies have not considered this traction effect. This paper proposes one numerical analysis procedure for investigating the friction's inverse influence on the sealing performance. The analysis procedure consists of three parts: dry traction analysis, basic film computational procedure and mixed-lubrication traction calculation. Characteristics of the O-ring seal, both with and without considering the traction effect, are presented and compared. Different friction coefficients, system pressures and velocities are also discussed. The results indicate that the traction produces a significant effect on seal performance and causes pronounced different influences for the outstroke and instroke. Highlights: A traction model is proposed to analyze the tractive effect induced by rod movement. Traction increases friction in the outstroke but decreases it in the instroke. Traction causes the contact pressure to incline to the stroke direction. Traction decreases the fluid transport both in the outstroke and in the instroke. In the instroke, torsion and displacement both occur at a low system pressure.